The least known with the smallest ranges: analyzing the patterns of occurrence and conservation of South American rodents known only from their type localities - Teta, Pablo; Dâ€™Elía, Guillermo (THERYA, 2019)
The identification of taxa with small range sizes is important both from an ecological and conservational perspective. As other small mammals, several species of rodents have restricted geographical distributions, a situation that could increase their immediate risk of extinction. Species having restricted ranges and/or low population sizes have usually lower genetic variation than wide-ranging relatives, being highly susceptive to disruptive treats, such as new or introduced competitors, pathogens, and predators, severe climatic events, cataclysms, and/or population-level phenomena. We reviewed the most recent compilations on South American rodents to identify those only known from their type locality (i. e., an area with a maximum latitudinal and longitudinal range of < 10 km). This restriction is in accordance with an extent of occurrence < 100 km2, which fits partially with the criterion B1 of the IUCN for an extent of occurrence of a critically endangered species. For each species, we recorded the year of description, country of origin, main habitat use, use of substrate, and conservation status. We identified 58 species of South American rodents that are known only from their type localities or their vicinities. These species belong to two suborders, seven families, and 29 genera. The family with more species in this list is Cricetidae, which accounted for a half of the included species. Most species in our list were described during the decades of 1890-1930 and 1990 to recent. The habitat type with more species in the list was tropical forest. Almost a third of the species are considered under the highest categories of threat, such as CR, EN o VU. Two species within the list are considered to become extinct in historical times, including the akodont Juscelinomys candango and the vizcacha Lagostomus crassus. Almost half of the species in our list are referred as DD. Fifty eigth rodent species from South American are only known from their type localities and their surroundings; i. e., ca. 9 % of the currently approximately 650 recorded species of the subcontinent. The species list provided here need to be depurated trough additional field and collection based work. Even when some species could be removed from this list (due taxonomical changes or additional records from other localities), it is also possible than others could be included. Most species in our list are found at or close to highland areas, such as the Andes or the Serra do Mar, suggesting that at least partially the rarity of some of them could be related to the relative inaccessibility of these places. As in previous contributions focused on geographically restricted taxa, most species in our list are considered as DD in the IUCN Red List. This is unfortunate, since species listed as DD usually do not gain much attention (i. e., conservation programs, founds) as those considered as CR, EN or VU. Previous authors discussed this point, suggesting the need to designate as CR all species geographically restricted to their type localities, at least when no recent records (i. e., in the last 25 years) exists.